Depressão pós-parto em mulheres vítimas de violência obstétrica: uma revisão de literatura - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Objective: to identify, in the evidence available in the literature, from 2013 to 2023, the types of obstetric violence and their relationship with postpartum depression. Methods: this is an integrative literature review of the exploratory descriptive type. The search was carried out in the Virtual Health Library databases, indexed in the National Library of Medicine of the National Institutes of Health of the United States, Online Scientific Electronic Library, Latin American and Caribbean Literature in Health Sciences and Database. The descriptors used were “Postpartum Depression” and “Obstetric Violence”. The search resulted in a total of 247 articles found in the databases; of these, 20 were selected following the inclusion criteria, submitted to detailed qualitative analysis. Results: through the analysis of the 20 publications included in this article, two analytical categories were constructed for discussion: Obstetric Violence and Postpartum Depression: Contextualization and 4 Interrelationship between obstetric violence and postpartum depression. In these categories, it can be identified that knowledge about the meaning of obstetric violence and its consequences can reduce psychiatric disorders in women in the puerperal phase. Conclusion: the present study found that postpartum depression, associated with obstetric violence, has the potential to cause hyperactivation, resulting in depressed mood, and can result in trauma for the rest of the woman's life.
Keywords: Depressão Pós-Parto; Violência Obstétrica; Maternidade; CNPQ::CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM DE SAUDE PUBLICA; ODS 3 – Saúde e bem-estar; ODS 5 – Igualdade de gênero; ODS 10 – Redução das desigualdades